KEPRIBADIAN TOKOH UTAMA DALAM NOVEL REMBULAN TENGGELAM DI WAJAHMUKARYA TERE LIYE (KAJIAN PSIKOANALISIS SIGMUND FREUD) - Maftuhah Maftuhah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This study aimed to describe the personality of the id, ego and super-ego character in the novel Rembulan Rey Drowning In Your Face Tere Liye work. This study was a qualitative descriptive study and included in this type of library research. The data used in this study is novel Rembulan Drowning In Your Face Tere Liye work. The data collection technique used is the technique of documentation and observation techniques.The results showed that the personality Ray in the novel Rembulan Drowning In Your face has the id that is present in the form of hatred against a dark past, the curiosity over his true identity, as well as the ambition to destroy those he considered duplicity. Ego Ray looked at the rebellion he often did to help the people he loved. Super ego Ray looked at the behavior that always decide things according to his conscience desires